Psychometric Properties of the German Version of the Perception of Interprofessional Collaboration Model-Questionnaire (PINCOM-Q) - Astrid Jörns-Presentati and Gunter Groen and Atle Ødegård (International journal of integrated care, 2021)
Objective: The Perception of Interprofessional Collaboration-Model Questionnaire (PINCOM-Q) measures professionals’ perceptions of interprofessional collaboration in the field of child and youth mental health. The aim of this study was to validate the PINCOM-Q in a sample of German child welfare and child and youth mental health professionals. Methods: The PINCOM-Q was translated into German and its underlying factor structure was examined using exploratory and confirmatory factor analysis. Results and discussion: Findings from this study suggest four factors (Interprofessional Climate, Conflict, Role Expectancy and Shared Goals, and Motivation) capture the concept of perceptions of interprofessional collaboration between child welfare and child and adolescent psychiatry. Conclusion: The use of PINCOM-Q (German) can be recommended as a research tool, investigating professional groups working with children and young people with multiple and complex needs.
Keywords: child welfare; child and adolescent psychiatry; interprofessional collaboration; validation; measurement